Названия членов русских политических партий и их отражение в польской прессе - Jóźwiak, Jolanta (Studia Rossica Posnaniensia, 2014)
The aim of this paper is to present the word formation strategies that are used to create the names of the members of Russian political parties. In the second part of the article the author focuses on difficulties associated with introducing these names into the Polish press with regard to their cultural connotations.